THE VERIDICAL MENTAL MAPS AS AN INPUT FOR THE URBAN DESIGN PROCESS: A Case Study of the Town of Gianyar Bali Indonesia - T. Nirarta Samadhi (DIMENSI (Journal of Architecture and Built Environment), 2001)
This study examines the veridicality of the mental maps of 100 residents of the town of Gianyar. In this case the veridicality measured was the level of accuracy of the Balinese worldview and cosmology captured by the mental maps. The information is useful for the urban design purposes, particularly as inputs in the maintenance of the cultural continuity of the Balinese urban environments.